PERENCANAAN PERBAIKAN GEDUNG PB. 4 & 5 PASAR BERINGHARJO YOGYAKARTA - , NOVA TRI UTOMO, Ir. Fathi Basewed, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The buildings are built as the public during ertain life time. But during his maid, buildings vulnerable to damage caused by several things. Based on the function of the building, Beringharjo market is used as a traditional shopping centre and it is an old building that is susceptible to damage, mainly on the structural damage. The building material suffered some damage is damage due to finishing work, seepage and degrad due to corrosion attack on steel reinforcing bars. Any attempted damage can be detected and treated as early as possible, so as not to cause greater damage that can trigger and exacerbate damage to the building. The purpose of the planning of repairs on the Beringharjo market is improving the quality and feasibility of building and reinforcing building structures.Improvements to the structure of the elements carried out on each type of damage with different methods appropriately and securely so that the use of a material improvement is not too extravagant. With the planned budget cost of the repair work can be seen the level of costs, and can serve as the value of the project. After planning the improvement of structure of beringharjo market, need for implementation in the field work was done based on the requirements laid out in the work plan and terms. The preparation of work plan and terms according to the formulation engineering building damage repair Beringharjo market.